Development of Integrated Online Course Learning (IOCL) Model to Improve Students' Literacy Skills in Digital Era 5.0 - Nurdyansyah Nurdyansyah; Arif Senja Fitrani; RR. Debby Amalia Azhari; Pandi Rais (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study aims to develop and analyse the feasibility, practicality and effectiveness of Integrated Online Course Learning (IOCL) application in improving students' digital literacy skills. This research uses the Research and Development (RnD) method using the ADDIE model, namely analysis, design, development, implementation, and evaluation. The data collection techniques used were questionnaires, document checklists and tests in the form of descriptive quantitative data. The analysis technique used in this research is mixed data analysis technique.  Based on the results of media expert validation, a value of 3.68 (92.18%) was obtained, which means very feasible, for the results of material expert validation obtained a value of 3.83 (95.71%) with a very feasible category, while the results of linguist validation obtained a value of 3.80 (95.00%) with a very feasible category. The practicality test of this product obtained a score of 94.64%, including in the category of very effective and practical to use. The results of the t-test showed a significant increase in students' digital literacy skills after receiving different treatments, namely using the IOCL Application. Based on the results of the t-test analysis of the average value of the control class 70.25 and the research class 87.50. Based on the data sig value. (2-tailed) or t-test p-value of 0.00 which means <0.05, it can be concluded that Ho is rejected and Ha is accepted. This shows: 1) This IOCL application has a positive influence on students' digital literacy skills, and 2) IOCL application has practicality, and effectiveness to be used as a learning model to improve students' digital literacy skills.